Ascorbic Acid Derivatives in the Sauvignon Blanc Cultivar (Vitis vinifera L.) During Berry Development in the Wellington and Elgin Regions - Dalicuba, M.; Nel, A.P.; van Jaarsvled, F.P. (South African Journal of Enology and Viticulture, 2021)
The exposure of grapevines to unfavourable conditions such as drought, high or low temperature and pathogenic attack increases the production of reactive oxygen species, thus inducing oxidative stress. One of the most important non-enzymatic antioxidants is ascorbic acid, which is used by plants to protect themselves against these toxic oxygen intermediates. DHA, DKG and threonate are ascorbic acid metabolites that are found during ascorbic acid catabolism. This study was done in two regions, the one in Wellington, classified as a warmer climate, and the other in Elgin, classified as a cooler climate. In each region, two Sauvignon blanc vineyard blocks were selected, with north to south and east to west row directions. Vines were monitored during the growing season to investigate the trends in the development of ascorbic acid metabolites in both regions. Canopy management practices were done at different ripening stages. Grape berries were sampled at different phenological stages according to the Eichhorn Lorenz scale: E-L 32, E-L 34, E-L 35, E-L 37 and E-L 38. Ascorbic acid derivative concentrations in the two regions varied significantly in that Elgin showed higher concentrations than Wellington at E-L 32 and E-L 38. Both the cool and warm regions had high concentrations of threonate, with no significant difference among stages of ripeness. The DHA, DKG and threonate levels were the highest at the E-L 32 phenological stage for both regions, with no significant differences among the other phenological stages, especially for DHA derivative concentrations. No significant effect on the DHA, DKG and threonate levels of the grapes was observed between row directions in each region.